The Energy Flux Different Stability Estimation Of Hydraulic Flow in a Horizontal Pipeline With Longitudinal Grooves Number Variation - Hadi, Abdul; Wardana, ING; Sutikno, Djoko (Jurnal Rekayasa Mesin, 2011)
The experimentally research was governed to estimate the external (source) and internal signal combined system without separate each other. Referring to that, the Lumped Parameter System (LPS) analytical modeling method by Matko et al (2001) as looked as possible is significance and accurately to estimate the internal pressure or difference pressure fluctuation of fluid lines. By using the LPS method were known that the horizontal fluid lines dynamic system with longitudinal grooves number variation (in fractal geometry image) for which will be used as an object in this research are fulfilled as a low frequency model class and small gain pressure fluctuation for every measurement acquisition result It’s properly in the LPS modeling method, the hydraulic fluid lines should be looked as a compressible fluid and over pass storage of energy charging so the response is not only affected by resistance but also by inductanc e and capacitance of the fluid. The three fluid elements respectively for a pipeline length unit are constant, have positive values eventually and modified as a function of the pipeline hydraulic diameter. It’s confirmed that the result could be given to predict the locally linearly stability character of the fluid flow energy flux different between upstream and downstream pipeline positions.Keyword: Energy flux different stability, hydraulic flow, horizontal pipeline, Longitudina grooves number variation, Lumped parameter system analytical modeling